STRATEGI PESANTREN MENGHADAPI PERUBAHAN MASYARAKAT - Ali Romdhoni (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2014)
The effort to maintain the sustainibility of pesantren needs hard-work and thought. Pesantren in Indonesia faces two problems. Pesantren must maintain its unique characteristics as religion education and moral shelter for society in one side. In other side, pesantren must be in line with the dynamic of society life in responding the development of ages. This article offers three things that must be responded by stakeholders of pesantren in order this institution can survive. Firstly, pesantren must consitently be an institution for cadering ulama. Secondly, pesantren must search the best method for learning and teaching continuously. Thirdly, pesantren can maintain as independent education institution.